Integrated ways of formation of the Uzbek national dance art - Iroda Nazarova (Genius Journals, 2022)
This article Uzbek dance free artist-artist, reverend format, The Uzbek dance school.
Keywords: Uzbek national dance art; spirituality; enlightenment; lifestyle